Smart Graphene Oxide Based Composite Materials and their Electric and Magnetic Stimuli-response. (2017) - Piao, Shang Hao; Choi, Hyoung Jin
Abstract: Compared to graphene, the functional groups of graphene oxide (GO) widen its application along with its GO-based composites in various engineering areas. Here, we briefly review their relatively new applications to the areas of both electrorheological (ER) and magnetorheological (MR) fluids under external electric or magnetic fields, respectively when they are dispersed in electrically or magnetically inert medium fluids. All the GO composites are found to exhibit improved ER characteristics compared to that of pure GO, while the GO can be adopted as either a coating layer or an additive in the carbonyl iron based MR fluids.